2017
DOI: 10.1158/1078-0432.ccr-16-0075
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Expression of Vitamin D Receptor and Breast Cancer Histopathological Characteristics and Prognosis

Abstract: Purpose Our previous work has shown low serum 25-hydroxyvitamin D concentrations in association with aggressive breast cancer subtypes. Vitamin D receptor (VDR) is central for vitamin D-mediated transcription regulation. Few studies have examined breast VDR expression with tumor characteristics or patient survival. Experimental Design VDR expression in breast tumor tissue microarrays was determined by immunohistochemistry in 1,114 female patients as low, moderate and strong expression based on an immunoreact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
76
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 41 publications
12
76
2
2
Order By: Relevance
“…An early study of 136 patients with primary breast cancer reported that women with VDR negative tumors relapsed significantly earlier than women with VDR positive tumors (22). In a more recent study of >1000 human breast cancers of mixed sub-types, Al-Azhri et al (23) reported that VDR expression was inversely related to tumor size, hormone receptor negativity and TNBC subtype. This is consistent with data showing that VDR protein expression declines in highly aggressive tumors (24; 25) and is deregulated by oncogenic transformation (26–28).…”
Section: Vdr Expression and Function In Normal And Neoplastic Breast mentioning
confidence: 99%
“…An early study of 136 patients with primary breast cancer reported that women with VDR negative tumors relapsed significantly earlier than women with VDR positive tumors (22). In a more recent study of >1000 human breast cancers of mixed sub-types, Al-Azhri et al (23) reported that VDR expression was inversely related to tumor size, hormone receptor negativity and TNBC subtype. This is consistent with data showing that VDR protein expression declines in highly aggressive tumors (24; 25) and is deregulated by oncogenic transformation (26–28).…”
Section: Vdr Expression and Function In Normal And Neoplastic Breast mentioning
confidence: 99%
“…Increased expression of VDR has been found in breast cancer and inversely related to aggressive tumor characteristics, including large tumor size, hormonal receptor (HR) negativity, triplenegative subtype [estrogen-receptor (ER) negative, progesterone receptor (PR) negative, and human epidermal growth factor receptor 2 (HER2) negative], and expression of proliferative marker Ki-67 (23). Similarly, various casecontrol studies suggested that the association between VDR polymorphism and risk of breast cancer may depend on race and ethnicity.…”
Section: Female Reproductive Tract Cancermentioning
confidence: 99%
“…Several studies have shown that the VDR is differentially expressed in benign and malignant breast tissue, suggesting a role for the VDR in transcriptional and cell-cycle regulation, as well as cell differentiation and apoptosis. (20)(21)(22)(23)(24) Thus, the degree of VDR expression in malignant tissues is inversely related to aggressive tumor characteristics, (25,26) ie, high expression levels are associated with slower cancer progression and longer survival. (15,20,27,28) In murine models of breast cancer, overexpression of the VDR reduces the incidence of pulmonary metastases (26) ; conversely, VDR ablation promotes primary tumor growth as well as lung and hepatic metastases.…”
Section: Introductionmentioning
confidence: 99%